Prevalance of Microalbuminuria in Children with Diabetes Melitus Type 1 - خوري, مها; رضوان, فيصل; حايك, بشرى (Latakia University Journal -Medical Sciences Series, 2021)
Objective: Diabetes is the most common endocrine disorder in childhood and adolescence. Diabetic nephropathy is the most common primary cause of the final stage of renal insufficiency in diabetics and it begins with a subclinical stage that is revealed by the presence of microalbuminuria, the aim of the study It is to determine the prevalence of micro albuminuria in children with type 1 diabetes. Method: A cross-sectional, descriptive observational study was conducted on 75 patients diagnosed with type 1 diabetes between 2018-2019 and the followers at the Diabetes Center in Lattakia city, between the ages of 6-14 years and the duration of the injury is more than one year. A 24-hour urine collection and micro albuminuria were calibrated on an automated chemistry system. The relationship between fine albuminuria and both the duration of the injury and the degree of diabetes control was studied. Results: the prevalence of microalbuminuria in children with diabetes mellitus type 1 was 9.3%. microalbuminuria was more frequent in children with a duration of diabetes of more than 5 years (P<0.05), and it was more frequent in children with poorly controlled diabetes.